Clinical Applications of Meshed Multilayered Anatomical Models by Low-Cost Three-Dimensional Printer. Issue 6 (29th November 2021) - Mitsuno, Daisuke; Ueda, Koichi; Nuri, Takashi; Katayama, Misato
Abstract : Summary: In recent years, even low-cost fused deposition modeling–type three-dimensional printers can be used to create a three-dimensional model with few errors. The authors devised a method to create a three-dimensional multilayered anatomical model at a lower cost and more easily than with established methods, by using a meshlike structure as the surface layer. Fused deposition modeling–type three-dimensional printers were used, with opaque polylactide filament for material. Using the three-dimensional data-editing software Blender (Blender Foundation, www.blender.org ) and Instant Meshes (Jakob et al., https://igl.ethz.ch/projects/instant-meshes/ ) together, the body surface data were converted into a meshlike structure while retaining its overall shape. The meshed data were printed together with other data (nonmeshed) or printed separately. In each case, the multilayer model in which the layer of the body surface was meshed could be output without any trouble. It was possible to grasp the positional relationship between the body surface and the deep target, and it was clinically useful. The total work time for preparation and processing of three-dimensional data ranged from 1 hour to several hours, depending on the case, but the work time required for converting into a meshlike shape was about 10 minutes in all cases. The filament cost was 2 to 8. In conclusion, the authors devised a method to create a three-dimensional multilayered anatomical model to easily visualize positional relationships within the structure by converting the surface layer into a meshlike structure. This method is easy to adopt, regardless of the available facilities and economic environment, and has broad applications.